2013
DOI: 10.1089/acm.2011.0908
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Yoga in Patients with Hypertension with Reference toGSTGene Polymorphism

Abstract: In conclusion, yoga has been found to decrease blood pressure as well as the levels of oxidative stress in patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Of note, this trial had 100% data ascertainment, over 80% compliance at each clinic visit, and measured blood pressure with an unattended manual device (a rigorous protocol with measurements 7–15 mm Hg lower than typical office readings). Other mind‐body interventions that involve both a physical and mental component have been associated with significant reductions in blood pressure, but the specific contribution of meditation and meditation‐like practices of inner focus and a concentration on the breath cannot be determined.…”
Section: Effects Of Meditation On Blood Pressurementioning
confidence: 99%
“…Of note, this trial had 100% data ascertainment, over 80% compliance at each clinic visit, and measured blood pressure with an unattended manual device (a rigorous protocol with measurements 7–15 mm Hg lower than typical office readings). Other mind‐body interventions that involve both a physical and mental component have been associated with significant reductions in blood pressure, but the specific contribution of meditation and meditation‐like practices of inner focus and a concentration on the breath cannot be determined.…”
Section: Effects Of Meditation On Blood Pressurementioning
confidence: 99%
“…Therefore, it is possible that yoga interventions in this study had a positive impact on the maternal stress and have reduced the sympathetic tone, which in turn relaxed the uterine arteries and resulted in a better blood flow. Yoga has been found to decrease blood pressure as well as the levels of oxidative stress in patients with hypertension [ 27 ]. This could have led to better trophoblast perfusion and less resistance in the uterine arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased level of MDA induces various cellular reactions which results in destruction of DNA and protein [23,24]. A study done among the healthy yoga practitioners has shown significant reduction in the level of MDA as compared with the control group (p<0.01) [25]. In another study done among prediabetic patients, 3-month practice of yogasanas and pranayama and shavasana resulted in significant reduction in malondialdehyde level (p<0.001) [18].…”
Section: Antioxidant Nature Of Yogamentioning
confidence: 99%